Aberrant crypt Foci segmentation using computational vision - Luís Filipe Ribeiro (2013)
Colorectal cancer is a type of cancer that develops in the large intestine (colon) or the rectum, one of the most common malignancies in the world. In this context, the aberrant crypt foci may have a crucial and decisive role. The aberrant crypt foci are supposed to be the precursors of colorectal cancer. This works aimed to develop computational methodologies for the detection and segmentation of aberrant crypt foci in endoscopy images.